Function mechanism of Y2O3 additive in silicon powder nitridation. Issue 4 (5th March 2019) - Jin, Xing; Xing, Pengfei; Zhuang, Yanxin; Kong, Jian; Jiang, Shengnan; Wei, Donghui
Abstract: Effect of sole Y2 O3 additive on the nitridation behavior of silicon powder was systematically studied using thermo gravimetry, differential thermal analysis, particle size analysis, X‐ray diffraction analysis, X‐ray photoelectron spectroscopy, scanning electron microscope and thermodynamic analysis in this paper. The thermo gravimetry results showed that Y2 O3 additive can significantly decrease the initial nitriding temperature and increase the nitriding rate. This phenomenon can be attributed to the much lower reaction temperature of the silica film and Y2 O3 additive than that of the silica film and silicon. In addition, Y2 O3 additive has little effect on the nitridation of silicon powder at 1300°C. However, it can obviously enhance the nitridation of silicon powder and the formation of β‐Si3 N4 at 1400°C, which is evidenced by the fact that the overall conversion increases from 58.1% to 100% and the fraction of β‐Si3 N4 in generated Si3 N4 increases from 7.9% to 68.2% with increasing the content of Y2 O3 additive from 0 to 10 wt%.